THE CAREER ADAPTABILITY POTENTIAL OF VOCATIONAL HIGH SCHOOL STUDENTS FROM A DIGITAL LITERACY PERSPECTIVE - Danis Rizki Swastika; Sudjani (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
The dynamic career world always raises a new career problem, especially now in the era of the industrial revolution 4.0 and society 5.0. Prospective job seekers, especially vocational high school students, must be able to adapt and have the skills to face career challenges in the digitalization era and achieve success in the school-to-work transition phase. This study aims to examine how the potential for career adaptability of vocational high school students is from a digital literacy perspective. This research method uses a descriptive correlational quantitative approach using the Career Adapt-ability Scale (CAAS) instrument developed by Savickas. This research was conducted on 534 students of class XII and XIII of SMKN 5 Bandung in the Academic Year of 2021-2022. The research findings show that digital literacy ability has a significant positive relationship to students' career adaptability with a correlation coefficient of 0.528, at a moderate level of relationship and the results of the analysis of the coefficient of determination show that digital literacy contributes 27.9% to career adaptability. This proves that digital literacy skills have a relationship and contribute to the potential adaptability of students' careers in facing career challenges in the 4.0 era.